Transgenic grapevines with decreased expression of tannin synthesis genes have altered grape and wine flavonoid composition. (12th November 2020) - Robinson, S.P.; Bogs, J.; McDavid, D.A.J.; Hooper, L.C.; Speirs, J.; Walker, A.R.
Abstract: Background and Aims: The flavonoid composition of grapes and wine was determined in transgenic grapevines with altered expression of the tannin synthesis genes anthocyanidin reductase (ANR) and leucoanthocyanidin reductase (LAR). Methods and Results: Shiraz grapevines were transformed with constructs aimed at decreasing expression of genes encoding VvANR and VvLAR1. Many of the ANRsi (silenced) transgenic lines had an altered appearance and a low concentration of leaf tannin but produced no fruit. Those that did produce fruit had a higher concentration of flavonol and a lower concentration of tannin in the skin but no change in seed or overall berry tannin. The ANRsi wines had a higher concentration of anthocyanin, flavonol, tannin and phenolic substances and higher colour. The LARsi lines had a lower concentration of tannin in the leaves and seeds but not in berry skins and produced wines with a lower concentration of anthocyanin, tannin and phenolic substances and lower colour. Conclusions: Manipulation of tannin genes altered flavonoid composition in grapevines and suggests that ANR is more important for tannin synthesis in leaves and berry skins whereas LAR1 is involved more in tannin production in seeds. Significance of the Study: There is potential to alter wine colour and tannin properties by manipulating the flavonoid pathway in grapevines.